Reflections on end-of-life dialysis - Castro,Manuel Carlos Martins (2018)
ABSTRACT The world population is aging and diseases such as diabetes mellitus and systemic arterial hypertension are increasing the risk of patients developing chronic kidney disease, leading to an increase in the prevalence of patients on dialysis. The expansion of health services has made it possible to offer dialysis treatment to an increasing number of patients. At the same time, dialysis survival has increased considerably in the last two decades. Thus, patients on dialysis are becoming more numerous, older and with greater number of comorbidities. Although dialysis maintains hydroelectrolytic and metabolic balance, in several patients this is not associated with an improvement in quality of life. Therefore, despite the high social and financial cost of dialysis, patient recovery may be only partial. In these conditions, it is necessary to evaluate the patient individually in relation to the dialysis treatment. This implies reflections on initiating, maintaining or discontinuing treatment. The multidisciplinary team involved in the care of these patients should be familiar with these aspects in order to approach the patient and his/her relatives in an ethical and humanitarian way. In this study, we discuss dialysis in the final phase of life and present a systematic way to address this dilemma.